Aircraft Identification Scheme using Public-KeyCryptosystem - Mohammed kaliphs, Saad (Journal of Engineering and Sustainable Development, 2005)
novel approach for identifying friend aircrafts from foe (IFF) using public-key cryptosystem is introduced. Tow schemes of public-key cryptosystem which provide higher security than convention(IFF) are presented computer simulation examples are also included to illustrate the identification procedure.